Syndrome Differentiation and Treatment of Chronic Urticaria Based on the “Xuanfu Theory” - Wang, Teng; Zou, Yaxin; Dong, Jundan; Zhang, Yiran; Liu, Yanting (Journal of Contemporary Medical Practice, 2026)
Chronic urticaria is a recurrent skin disorder with limited long-term efficacy of conventional antihistamine treatment. As a core traditional Chinese medicine framework, Xuanfu theory effectively elucidates the holistic pathogenesis of chronic urticaria and guides its comprehensive management. This review systematically summarizes recent advances in the Xuanfu-based diagnosis and treatment of chronic urticaria. Dysregulated Xuanfu opening-closing and qi-fluid stagnation constitute the fundamental pathogenesis, involving excess and deficient stagnation, latent wind retention, and collateral wind agitation. The unified therapeutic principle of unblocking Xuanfu covers multiple internal herbal strategies centered on wind medicinals, as well as standardized external interventions including acupuncture and cupping. Current clinical evidence demonstrates that Xuanfu-oriented treatment achieves comparable short-term efficacy with Western medicine and yields significantly lower recurrence rates via regulating Th1/Th2 immune balance. However, existing studies are limited by insufficient high-level clinical trials, unclear molecular mechanisms, and incomplete syndrome-based research. Further rigorous clinical and experimental investigations are required to standardize and modernize the TCM treatment of chronic urticaria.